2015
DOI: 10.3945/jn.114.202630
|View full text |Cite
|
Sign up to set email alerts
|

Protein Deficiency and Intestinal Nematode Infection in Pregnant Mice Differentially Impact Fetal Growth through Specific Stress Hormones, Growth Factors, and Cytokines>

Abstract: PD and nematode infection impaired fetal mass and linear growth, respectively. Fetal mass, length, and individual organ masses were regulated by different hormones, growth factors, and cytokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 58 publications
(72 reference statements)
1
12
1
1
Order By: Relevance
“…The levels of IGF-1 increased with increasing Hb, and when the concentration of Hb exceeded a certain range, with the increase in Hb, IGF-1 decreased instead. Previous studies have shown that high Hb may impact the growth and development of children through mechanisms including inflammation, which may impair growth and development [16]. Our findings suggested that a too high of Hb is associated with reduced IGF-1 levels.…”
Section: Discussionsupporting
confidence: 52%
“…The levels of IGF-1 increased with increasing Hb, and when the concentration of Hb exceeded a certain range, with the increase in Hb, IGF-1 decreased instead. Previous studies have shown that high Hb may impact the growth and development of children through mechanisms including inflammation, which may impair growth and development [16]. Our findings suggested that a too high of Hb is associated with reduced IGF-1 levels.…”
Section: Discussionsupporting
confidence: 52%
“…28,30,33,36 In three studies, the metabolic/nutritional exposure and the infectious exposure had additive effects without synergizing or antagonizing one another. 30,32,34 In two studies, zinc supplementation, which had no effect on its own, reversed the effect of LPS. 28,33 As already mentioned, two studies showed that maternal immune activation could reverse the effects of diabetes and iron deficiency.…”
Section: Animal Study Resultsmentioning
confidence: 99%
“…In this survey, HIV was not associated with an increased risk of spontaneous or provider-initiated PTB, consistent with Ndirangu et al 22 These findings reinforce the trend of PTB associated with small maternal stature and maternal infections demonstrated in the Tellapragada study. 25 Outcomes of maternal immune activation and metabolic abnormality in model systems A total of six studies were performed in mice, [28][29][30][31][32][33] two in rats, 34,35 and one in sheep 36 (Table 4). The rat studies both involved nutritional deficiency, while the sheep study and two of the mouse studies involved supplementation.…”
Section: Individual Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, mRNA expression and protein levels of FGF2 are increased in the endometrium in heifer cows fed a lower (protein 10% of dry matter) protein diet in comparison to lactating cows fed a greater (18% protein of dry matter) percentage protein diet (Pretheeban et al, 2011). Likewise, pregnant mice fed a protein deficient diet displayed an increased FGF2 concentration in the amniotic fluid (Starr et al, 2015). Complicated pregnancies involving intrauterine growth restriction have increased vasculogenesis, angiogenesis, and pseudovasculogenesis via the increased expressions of VEGF-A, FGF2, and eNOS (Barut et al, 2010).…”
Section: Discussionmentioning
confidence: 97%